2022
DOI: 10.3390/cancers14143472
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Landscape, Clinical Features and Outcomes of Non-Small Cell Lung Cancer Patients Harboring BRAF Alterations of Distinct Functional Classes

Abstract: Background: In non-small cell lung cancer (NSCLC), BRAF class 1 alterations are effectively targeted by BRAF inhibitors. Conversely, targeted therapies have very low or absent activity in patients carrying class 2 and 3 alterations. The spectrum of BRAF alterations in NSCLC patients, and their accompanying clinical features, genomic landscape and treatment outcomes have been poorly reported. Patients and methods: We identified BRAF alterations of defined functional class across different tumors through a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Smoking history can be associated with BRAF mutations, as well as KRAS, MET , and other mutations 9 , 28 , 29 . However, a few studies have also suggested that BRAF V600E is less associated with smoking history than other BRAF mutations 26 , 30 , 31 . Therefore, all patients with advanced NSCLC regardless of smoking history should undergo broad-based mutation testing, including BRAF 5 , 21 , 22 .…”
Section: Braf-mutant Metastatic Nsclc Disease Overviewmentioning
confidence: 99%
“…Smoking history can be associated with BRAF mutations, as well as KRAS, MET , and other mutations 9 , 28 , 29 . However, a few studies have also suggested that BRAF V600E is less associated with smoking history than other BRAF mutations 26 , 30 , 31 . Therefore, all patients with advanced NSCLC regardless of smoking history should undergo broad-based mutation testing, including BRAF 5 , 21 , 22 .…”
Section: Braf-mutant Metastatic Nsclc Disease Overviewmentioning
confidence: 99%
“…Recently, an analysis of patients ( n =35) carrying non-V600 mutations enrolled in the POPLAR and OAK phase II and phase III trials on second-line atezolizumab 85 , 86 reported shorter OS than that of patients with wild-type BRAF (8.4 versus 11.5 months; HR 1.70 (95% CI 1.19–2.44); p =0.0033). 87 …”
Section: Reviewmentioning
confidence: 99%
“… 78 Similarly, in a cohort of 139 patients with BRAF -mutant NSCLC, median TMB was significantly higher in class 3 than in the other classes ( p <0.001). 87 …”
Section: Reviewmentioning
confidence: 99%
“…On the contrary, substitutions present in other codons of BRAF genes do not seem to have the oncogenic potential [ 7 , 9 ]. According to their activity, BRAF mutations have been classified into three functional classes [ 9 , 12 , 13 ]: (i) class 1 BRAF mutations (BRAF p.V600), RAS independent, signal as monomers, and characterized by strong activity of BRAF kinase domain; (ii) class 2 BRAF alterations, RAS independent, signal as constitutive dimers, and with intermediate to high activity of BRAF kinase domain; (iii) class 3 BRAF alterations, RAS dependent, characterized by low or absent kinase activity.…”
Section: Introductionmentioning
confidence: 99%